2017
DOI: 10.1039/c7tc02655b
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular states in organic dye dispersions: excimers vs. aggregates

Abstract: Efficient energy transfer in dispersed films of organic dyes to dark excimer sites and highly emissive J-coupled dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 41 publications
10
78
0
Order By: Relevance
“…Other authors have also observed that BODIPY dyes of LBDP1 type can show excimer fluorescence at high local concentrations when performing studies in membranes. [57][58][59] Chujo et al studied the aggregation behaviour of a series of amphiphilic LBDP3 dyes (with different PEG substituents) in mixtures of THF:water. [20] One of these BODIPYs showed aggregates derived from H dimers, forming spherical nanoparticles in aqueous THF (with a diameter of 3.9 � 0.6 nm, assembling into larger aggregates of ca.…”
Section: Previous Observations On Associationmentioning
confidence: 99%
“…Other authors have also observed that BODIPY dyes of LBDP1 type can show excimer fluorescence at high local concentrations when performing studies in membranes. [57][58][59] Chujo et al studied the aggregation behaviour of a series of amphiphilic LBDP3 dyes (with different PEG substituents) in mixtures of THF:water. [20] One of these BODIPYs showed aggregates derived from H dimers, forming spherical nanoparticles in aqueous THF (with a diameter of 3.9 � 0.6 nm, assembling into larger aggregates of ca.…”
Section: Previous Observations On Associationmentioning
confidence: 99%
“…However, we cannot exclude the presence of excimers as a result of  stacking in the excited state (in closely packed aggregates subtle changes in the geometrical arrangement can lead to differential excimer-formation capability), 12,24 since it also provides red-shifted emission patterns, albeit usually with lower fluorescence-deactivation probability than that provided by J-like aggregation. 23 To Figure 3a and corresponding spectra in Figure 3b). Thus, at the fiber ends (see Figure 3a) the fluorescence profile is dominated by the characteristic short-wavelength emission from individual 1 molecules (longer lifetimes), whereas the characteristic red-shifted emission from 1 aggregates prevails at the center of the particle (faster lifetimes).…”
Section: Resultsmentioning
confidence: 99%
“…Upon the excitation at the vibrational absorption peaks, mirror-imaged fluorescent emission spectra are observed in both molecules, peaking at 686 and 706 nm in the deep red region, respectively, with Stokes-shifts of 216 and 245 cm À1 . [28] Their absorption and emission properties are further investigated in solid state. Although the photoluminescent quantum yields (PLQYs) of red emitters usually suffer from the non-radiative deactivation due to the energetically close lying emissive state and high vibronic state of the ground state, BF-BDP and NF-BDP present decent PLQYs of 0.39 and 0.45, respectively, when taking ZnPc (zinc phthalocyanine) as the reference ( Figure S2).…”
Section: Highly Efficient Deep-red-to Near-infrared-absorbing and Emimentioning
confidence: 99%